Overall survival after treatment failure among patients with rectal cancer: original investigation - Diefenhardt, Markus; Martin, Daniel; Fleischmann, Maximilian; Hofheinz, Ralf-Dieter; Ghadimi, Michael; Rödel, Claus; Fokas, Emmanouil (JAMA network open, 2023)
Oncologic outcomes among patients with rectal cancer after developing local recurrence and/or distant metastases remain poorly studied.To analyze the trend of overall survival after treatment failure for patients with rectal cancer within three consecutive phase 2 or 3 trials of the German Rectal Cancer Study Group.This cohort study is a post hoc analysis of 3 randomized phase 2 or 3 trials (CAO/ARO/AIO-94, -04, and -12 trials, conducted in Germany) that included 1948 patients with locally advanced rectal adenocarcinoma. The CAO/ARO/AIO-94 trial recruited patients between February 1995 and September 2002, the CAO/ARO/AIO-04 trial recruited patients between July 2006 and February 2010, and the CAO/ARO/AIO-12 trial recruited patients between June 2015 and January 2018. Statistical analysis was conducted between September 2022 and March 2023.A total of 119 of 391 patients in the CAO/ARO/AIO-94 trial group A, 295 of 1236 patients in the CAO/ARO/AIO-04 trial, and 69 of 306 in the CAO/ARO/AIO-12 trial experienced treatment failure (R2 resection or local recurrence or distant metastases) and were included in further analyses.Characteristics of treatment failure and overall survival were assessed in all 3 trial cohorts.Of the 1948 patients treated in the 3 trials, 15 were excluded because of missing data. Of the remaining 1933 patients (median age, 62.5 years [range, 19-84 years]; 1363 men [71%] and 570 women [29%]) with locally advanced rectal adenocarcinoma (cT3 or 4 or cN+) treated within 3 consecutive clinical trials, 483 experienced treatment failure and were analyzed. After a median follow-up of 36 months (IQR, 24-51 months) for all patients, overall survival after treatment failure was significantly improved in the CAO/ARO/AIO-04 trial (at 3 years, 44% [IQR, 37%-51%]; hazard ratio [HR], 0.61 [95% CI, 0.47-0.79]) and further improved in the CAO/ARO/AIO-12 trial (at 3 years, 73% [IQR, 60%-87%]; HR, 0.32 [95% CI, 0.18-0.54]) compared with the CAO/ARO/AIO-94 trial (at 3 years, 30% [IQR, 22%-39%]) (both P < .001). Distant metastasis was the main reason for treatment failure throughout a 5-year follow-up (range, 67%-87%), and the relative risk for treatment failure was highest in the first 18 months in all 3 trials. ypTNM stage was significantly associated with the risk and time interval to treatment failure. Improvement in overall survival after treatment failure was independent of sex.This cohort study suggests that advancements in salvage strategies during the past decades have likely improved overall survival among patients with rectal cancer who experienced treatment failure.
Gesehen am 16.07.2024